THE INFLUENCE OF PREDICT-SCAN-READ-ANSWER (PSRA) STRATEGY AND CREATIVE THINKING TOWARD THE ELEVENTH GRADERS’ READING COMPREHENSION AT SRIGUNA SENIOR HIGH SCHOOL OF PALEMBANG - Santi Mayasari (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT This research was conducted to investigate the influence of Predict-Scan-Read-Answer (PSRA) Strategy and Creative Thinking toward the Eleventh Graders’ Reading Comprehension at Sriguna Senior High School of Palembang. This research applied experimental method with factorial design. There were 280 students as the population. From 280 students, 80 students were taken as the samples of this research by using two stage random sampling. The statistical analyses used were Independence t-test and Two-way ANOVA. The distribution of both experimental and control group score were normal, since the significant value was higher than 0.05. The data of PSRA strategy and conventional strategy were homogeneous since the result of homogeneity of variance testing indicated that the significant value of all the data was higher than the significant of p-output (0.05).            Furthermore, it was found that (1) there was a significant difference in reading comprehension achievement between high creative thinking and low creative thinking students who were taught through PSRA Strategy. (2) There was a significant difference in reading comprehension achievement between high creative thinking and low creative thinking students who were taught through Conventional Strategy. (3) There was a significant difference in means score between students who had high creative thinking, taught through PSRA strategy and Conventional Strategy. (4) There was no significant difference in means score between students who had low creative thinking, and those who were taught using PSRA strategy and Conventional Strategy. (5) There was a significant interaction effect (influence) of PSRA strategy and Creative Thinking on reading comprehension. Key Word: Predict-Scan-Read-Answer (PSRA), Creative Thinking, Reading Comprehension